Stand Regeneration Characteristics of Beech and Fir Forests in Gorski Kotar Region - Krunoslav Teslak; Mislav Vedriš; Marko Gašparović; Marijana Žunić; Jura Čavlović (South-East European Forestry, 2016)
Background and Purpose: Beech-fir forests cover about 13% of forest land in Croatia, thus being a significant forest resource that is dominantly managed by uneven-aged selection management system. Continuous and successful regeneration is an essential prerequisite for this kind of forest management. Therefore updated and sound information on the present state of regeneration is important, especially in the context of climate change and the actual structure of beech and fir forests. The aim of this paper is to present and analyse current state of regeneration in beech and silver fir forests of Gorski kotar region, with regard to forest ownership (management model), forest communities and habitat characteristics. Materials and Methods: Field measurement has been done on 313 plots in the beech and fir forests of Gorski kotar region, Croatia. The assessment of regeneration was based on measurement of trees ranging from 0 to 10 cm dbh (species, number of trees, average height) and also the estimation of seedlings up to 1.30 m high (regenerated area in 10% classes, the share of tree species, the origin of stand establishment, regeneration quality). Results: Attributes like the success of regeneration, the structure of seedlings by species and the recruitment of saplings were analysed with regards to ownership, forest communities and the aim of forest management. The results indicate poor incidence of regeneration especially of silver fir (more than 50% percent of field plots with no regeneration). Silver fir saplings (height>1.3 m, dbh ≤10 cm) are registered on 9% of plots, average number being only 165 per ha (all species together 2044 per ha). The estimated average share of the regenerated area is 16.3% of total forest area, contributed by 5.2% of conifers and 3.8% silver fir. A total of 14 tree species were recorded on regenerated areas, clearly dominated by broadleaves, especially beech (over 50%). Conclusions: Significant differences in regeneration attributes were proven by ANOVA between ownership categories, forest communities and habitat characteristics. In order to get better insight on the structure of regeneration, it is recommended to improve future assessment by establishing special sub-plots for measurement of seedlings by species.